Content analysis of different types of nirmana teaching videos and the viewers’ perception - Ardianto, Deny Tri; Wicaksono, Arif Ranu; Mataram, Sayid; Widayat, Rahmanu; Yuda, Jotika Purnama (Dewa Ruci: Jurnal Pengkajian dan Penciptaan Seni, 2024)
Nirmana is a mandatory basic competency for academic artists. Strengthening the basics of Nirmana is compulsory so that fine artists and designers maintain their bargaining position in society. One of the rising media to learn Nirmana is teaching videos available on online platforms such as YouTube. With the many types and styles of Nirmana learning videos available on YouTube, a study to analyze which type of videos are effective in learning Nirmana is needed. This study uses content analysis to classify videos that convey information about Nirmana into four groups: live demonstration videos, animated videos, conventional lecture videos, and tutorials (Step-by-step). To determine the video's effectiveness, the responses from viewers were analyzed using a pragmatic approach. From the analysis results, teaching videos in the form of live demonstrations, animations, and tutorials proved to be the most effective in assisting viewers to learn about Nirmana. Videos with these concepts can convey information in an engaging, clear, and visually understandable way, thus improving student understanding more effectively. Integrating the appropriate teaching videos into the Nirmana curriculum, such as live demonstrations for practical projects and animated videos or tutorials or theory, can help students understand Nirmana better.